2019
DOI: 10.4070/kcj.2019.0234
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Stroke Risk in Atrial Fibrillation: Adherence to Guidelines Has Improved, but Patient Persistence with Anticoagulant Therapy Remains Suboptimal

Abstract: No changes have been made to this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 111 publications
(287 reference statements)
5
53
0
2
Order By: Relevance
“…A gradual increase in the proportion of DOAC usage in AF treatment was recently documented all over the world [ 11 , 12 , 13 ]. DOACs are initiated more frequently than VKA in numerous countries [ 11 , 13 , 14 ], contributing to an increase in appropriate prescribing of anticoagulants in AF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A gradual increase in the proportion of DOAC usage in AF treatment was recently documented all over the world [ 11 , 12 , 13 ]. DOACs are initiated more frequently than VKA in numerous countries [ 11 , 13 , 14 ], contributing to an increase in appropriate prescribing of anticoagulants in AF.…”
Section: Discussionmentioning
confidence: 99%
“…A gradual increase in the proportion of DOAC usage in AF treatment was recently documented all over the world [ 11 , 12 , 13 ]. DOACs are initiated more frequently than VKA in numerous countries [ 11 , 13 , 14 ], contributing to an increase in appropriate prescribing of anticoagulants in AF. Despite DOACs’ current large availability and the increasing adherence to anticoagulation guidelines, sub-optimal anticoagulation in AF [ 13 , 15 ] and inappropriate use at DOAC initiation still represent pertinent issues [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,112,113 Patient-level factors also contribute to poor adherence and persistence to treatment, such as financial barriers or treatment burden. 115 Failure to reduce the dose of NOACs in patients with renal disease, in whom it is indicated, may result in an increase in the risk of bleeding; in contrast, inappropriate dose reduction, that is, inconsistent with the label, may decrease the effectiveness of stroke prevention. 38 Results from a large real-world cohort study demonstrated that lower doses of apixaban in patients with normal or mildly reduced renal function were found to increase the risk of stroke by approximately five times compared with the standard dose.…”
Section: Stroke Risk and Noac Dosingmentioning
confidence: 99%
“…Оральные антикоагулянты (АК) эффективно снижают риск ишемического инсульта у пациентов с ФП [4], однако недостаточный охват антикоагулянтной терапией (АКТ) [1], назначение субтерапевтических доз АК [2,3] и неудовлетворительная приверженность АКТ [4] могут ослабить профилактический эффект. По разным данным, 25-50% пациентов с ФП, нуждающихся в АК, не получают терапию [5,6]. Чаще всего это связано с пожилым возрастом пациента, высоким риском кровотечения (из-за онкологических заболеваний, высокого риска падений и т.д.…”
Section: ââåäåíèåunclassified